Value System of Citizens of Montenegro - Radovanović, Dobrivoje; Radulović, Danka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2005)
Montenegro’s citizen value system was explored on the random sample consists of 794 subjects taken from the population of adult inhabitants of this Republic. The sample of value concepts was chosen on the basis of Rokeach’s model and definition of the values. In comparison with the original sample of value of this author, our list of value concepts was changed by including 11 new concepts in accordance with the specificity of given cultural environment. In this research we applied particular questionnaire which means that values were explored using paper-pencil system and not the system of cards as it was the case in the original researches of the author. Results of the research were compute employing component analyses and rotation of the main component in OBLIVAX position. We found out four reliable and well structured factors which could be identificated as 1. Patriotic values; 2. Personal values; 3. Moral-religious values and democratic-humanistic values.